Kepastian Hukum Bagi Konsumen Apabila Pengembang Perumahan Dinyatakan Pailit - Ira Rizky Firdaus (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2021)
ABSTRACT This study raises the issue of, first, the failure of the delivery of housing units by housing developers can be categorized as debt in bankruptcy. Second, the status of home ownership that has been purchased by consumers if in the middle of the road housing developers are declared bankrupt. Third, settlement efforts that can be done by consumers if the housing developer is declared bankrupt. This research is a doctrinal law research that uses a statutory approach and a conceptual approach. The results of the study concluded, first, the failure of housing developers to hand over housing units to consumers categorized as debt in bankruptcy because the Bankruptcy Act defines debt in a broad sense so that any form of achievement can be called debt in bankruptcy. Second, the status of ownership of home units that have been purchased by consumers if the housing developer is cut off is still the property of the housing developer completely, because the basis of consumer rights is still in the form of a Binding Sale and Purchase Agreement (PPJB). As a result the unit of the house will become a bankrupt property that will be dealt with by the Curator to pay the debts of housing developers to the creditors. Third, based on the provisions in the Bankruptcy Act, the state of the housing developer that has been cut off resulting in PPJB will automatically become removing and consumers can apply as concurrent creditors for compensation. While according to the Consumer Protection Act, there is no regulation regarding settlement efforts that consumers can make when housing developers are bankrupt, so settlement efforts that can be made by consumers are based solely on the provisions in the Bankruptcy Act.